The Influence of Sports on the Construction of a Good Psychological Atmosphere in Chinese International Education from the Perspective of Intercultural Communication - Yuemiao Liu; Meiyu Wang (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
Culture is inescapable in education, incorporating cross-cultural dialogue and serving as the foundation of Chinese foreign education (CIE). This study aims to investigate, from the standpoint of intercultural communication, the impact of sports on the development of a positive psychological climate in CIE. The study employed quantitative and qualitative methods, collected data through tests, classroom observation, and interviews, and conducted a quasi-experimental comparison of the experimental group learning CIE and culture curriculum and the control group learning traditional language skills curriculum. This study determined that the experimental group's cross-cultural attitude improved more rapidly after the systematic study of cultural courses, which plays a more significant influence in fostering a positive psychological climate in CIE. In addition, the study indicated that culture is transmitted through language and that cultural elements play an essential role in language acquisition. In addition, most learners of a second language originate from nations and areas with different cultural backgrounds than the target language. Comparing one's culture with students and determining the most effective cross-cultural communication strategies are essential for teaching.